NETWORK ANALYSIS OF ANXIETY, DEPRESSION, COPING STRATEGIES, AND SOCIAL SUPPORT: A GENDER COMPARISON AMONG HIGH SCHOOL STUDENTS IN HO CHI MINH CITY. (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the network models of anxiety, depression, social support, and coping strategies among high school students in Ho Chi Minh city by gender.Method: A cross-sectional study was conducted among 1081 high school students in Ho Chi Minh city, utilizing the PHQ-9, GAD-7, CSI, and MSPSS scales. Network structures were estimated via Gaussian Graphical Models and gender differences were evaluated using the NetworkComparisonTest in R.Results: The overall network structure was comparable between males and females. However, maladaptive coping strategies occupied central positions within the networks and differed by gender. In males, self-blame emerged as the primary central node, whereas in females, wishful thinking was most central, both were positively associated with anxiety and depression.Conclusions: Maladaptive coping strategies were identified as central nodes within the network. Interventions targeting these gender-specific central nodes, while concurrently strengthening adaptive coping and social support, may contribute to improved mental health outcomes among adolescents.
Keywords: Anxiety, depression, coping strategies, social support, network analysis, gender differences.